Smartboard enhanced creativity in the technology classroom: lessons on mechanical systems and control - Ndwandwe, Khanyisile Precious; Ramaligela, Manto Sylvia; Mtshali, Thokozani Isaac (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
Creativity is significant in education as it makes learners to fully concentrate throughout the learning and teaching process. Hence, the purpose of this study was to explore the effectiveness of smart board in enhancing Technology teachers’ creativity in the classroom. The theory of creativity was used as a lens to view the study, and the 9E instructional model which was used to guide and understand classroom activities. The study used a qualitative research approach and the case study design to gather and analyze data. The semi-structured interviews were used to collect data from four schools which were purposively sampled because they had smart boards. Four Technology teachers and eight learners were the participants in the study. To analyze the data, deductive content analysis was used. The findings of the study revealed that both teachers and learners perceived the smart board as effective in enhancing Technology teachers’ creativity in the classroom. Teachers and learners indicated that smart board can present lessons more interesting, exciting, effective and develop learners’ creative thinking skills. They could access the internet to search for online resources which include but are not limited to diagrams, pictures, online quizzes and YouTube videos to creatively present their lessons in the classroom. Different smart board programs such as the smart notebook, animation, PowerPoint presentations, and the show and hide feature can be used to enhance creativity. With the help of the smart board, teachers can use a variety of teaching methods to correct learners’ misconceptions and further develop their creative thinking skills.